Management of Acute Migraine in Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The management of acute pediatric migraine headaches in the pediatric emergency department (ED) and in a mixed pediatric and adult ED was compared at the University of Alberta, Edmonton, Canada.